Environmental risk communications : waste, incineration and dioxins - Rourke, Joanne (Trinity College (Dublin, Ireland). Department of Geography, 2010)
Industrialisation and modern technologies have contributed to economic and social progress, but the benefits are being eroded by the environmental and health risks associated with these technologies. Against this backdrop, risk has periodically moved to the fore of political debate, and publics have become more questioning of science and technology making it difficult for decision-making about technology to remain outside democracy. Research suggests that psychological and broader socio-cultural factors influence publics’ risk perceptions more than calculable risk probabilities. The gap between technical risk assessments and ‘lay’ perceptions of risks means that risk communication is crucial to decisions about technologies perceived as hazardous. The receipt of risk information is shaped by factors such as trust and transparency. Thus the role of institutional politics and issues of procedural justice have become important facets of the development of controversial facilities. Consequently, analysts are calling for more research attention to why publics lack trust in risk assessment and risk regulatory systems.
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin